Complete genome sequence of a new circular DNA virus from grapevine - Krenz, Björn; Thompson, Jeremy R; Fuchs, Marc; Perry, Keith L (Journal of virology, 2012)
A novel circular DNA virus sequence is reported from grapevine. The corresponding genomic organization, coding potential, and conserved origin of replication are similar to those of members of the family Geminiviridae, but the genome of 3,206 nucleotides is 4% larger than the largest reported geminiviral genome and shares only 50% overall sequence identity.